2012
DOI: 10.1158/1078-0432.ccr-12-1157
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Kinome shRNA Screening Identifies CDK11 (PITSLRE) Kinase Expression Is Critical for Osteosarcoma Cell Growth and Proliferation

Abstract: Purpose: Identification of new targeted therapies is critical to improving the survival rate of patients with osteosarcoma. The goal of this study is to identify kinase based potential therapeutic target in osteosarcomas.Experimental Design: We used a lentiviral-based shRNA kinase library to screen for kinases which play a role in osteosarcoma cell survival. The cell proliferation assay was used to evaluate cell growth and survival. siRNA assays were applied to confirm the observed phenotypic changes resulting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 35 publications
7
64
0
3
Order By: Relevance
“…3 In this study, the optimization electroporation parameter applied was: pulse voltage, 1230; pulse width, 10; pulse number, 4, which achieved 70–80% transfection (data not showed). KHOS and U-2OS cells were successfully transfected with CDK11-Cas9-GFP or pEGFP-N3.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…3 In this study, the optimization electroporation parameter applied was: pulse voltage, 1230; pulse width, 10; pulse number, 4, which achieved 70–80% transfection (data not showed). KHOS and U-2OS cells were successfully transfected with CDK11-Cas9-GFP or pEGFP-N3.…”
Section: Resultsmentioning
confidence: 87%
“…In an effort to identify new therapeutic targets in osteosarcoma, we found that knockdown of CDK11 (cyclin-dependent kinase 11, also known as CDC2L for cell division cycle 2-like or PITSLRE) by short hairpin RNA (shRNA) or short interfering RNA (siRNA) inhibited tumor cell growth and induced apoptosis. 3 Importantly, nuclear CDK11 expression levels correlated with clinical prognosis in osteosarcoma patients. Systemic in vivo administration of in vivo ready CDK11 siRNA reduced tumor growth in an osteosarcoma xenograft model.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of the human TFAP2B-specific siRNA was 5′-GGA CCA GUC UGU CAU UAA ATT-3′ and 5′-CCC GAA AGA AUA UGC UGU UTT-3′, and the scramble siRNA was 5′-UUC UCC GAA CGU GUC ACG UTT-3′. The siRNA and plasmid were incorporated with additional chemical modifications for superior serum stability in the in vivo applications, and the knockdown efficiency was validated in vitro [28,29]. For the in vivo delivery of the siRNA and plasmid into tumors, the sequences were first encapsulated into DOTAP-cholesterol (DC) (Avanti Polar, Birmingham, AL, USA) nanoparticles that had validated by many analyses by dissolving in sterilized de-ionized water and then mixing with the nanosomes.…”
Section: Methodsmentioning
confidence: 99%
“…In previously work we screened osteosarcoma cell lines with the lentiviral shRNA kinase library, consistently identifying that knockdown of CDK11 expression led to inhibited growth and induction of apoptosis in both in vitro and in vivo models [17]. CDK11 (formerly known as PITSLRE or CDC2L1) is a member of the extended family of p34cdc2-related kinases [18].…”
Section: Introductionmentioning
confidence: 99%